PEDAGOGICAL FUNDAMENTALS FOR THE DEVELOPMENT OF CRITERIA FOR PROFESSIONAL ACCREDITATION OF EDUCATIONAL PROGRAMS - Alexander I. Chuchalin; Polina S. Shamritskaya (Высшее образование в России, 2016)
The criteria for professional accreditation of engineering programs of secondary and higher vocational education and also the pedagogical fundamentals of their development by the Association for Engineering Education of Russia (AEER) are given in the paper. The criteria are recommended to be applied in higher education institutions and colleges when designing new and updating existing educational programs as well as for the design of pedagogical learning environment necessary for program implementation and quality assurance.